Deterioration and preservation of wood by using natural preservatives of potential interest in Brazil - Gonçalves, Débora; Rocco Lahr, Francisco Antonio (BOSQUE, 2020)
In this review article, the main deterioration processes and uses of natural preservatives in wood are discussed, in particular in Brazil, taking into account its economic relevance in Latin America. It contextualizes the problem of protection and chemical degradation of wood, topics of interest not only in Brazil but also in other countries. In addition, the use of novel products is discussed, such as neem oil, castor oil, pepper extracts, tannins, tall oil, linseed oil, oils extracted from native timbers, chitosan and others. In terms of solutions, more studies are necessary in the field and modification of formulations with fixation agents, biocides, antioxidants, additives and others. In addition, the legal aspects of commercialization for new formulations in countries rich in natural resources, though underdeveloped, must be taken into account.